Synthesis and characteristics of nanostructured silicon-rich nitride thin films using modified long-wavelength CO2 laser annealing. (25th August 2015) - Chung, C K; Li, C H; Chen, T S
Abstract: The silicon nanocrystals (nc-Si) or nanoparticles (np-Si) surrounded by a dielectric matrix of SiN x or SiO x were traditionally synthesized by chemical vapor deposition and subsequent furnace annealing at a high temperature of 1000 °C on the whole wafer. The short-wavelength (248 nm) KrF excimer laser could also be used for assisting annealing. In this article, the unique method of glass assisted long-wavelength (10.6 μ m) CO2 laser annealing through local heating was applied to produce crystallized np-Si on sputtered silicon-rich nitride (SRN) thin films. Various CO2 laser fluences were irradiated on SRN films for studying the evolution of the microstructure and optoelectronic characteristics of films. The size of np-Si on SRN films increases with the laser fluence. According to the photoluminescence (PL) and bonding configuration results, two broad-visible PL spectra of the films were deconvoluted into three bands within wavelengths of 350 650 nm linked to the unsatisfied interface states, the located states related to the mixed Si–O or Si–N bonds in the SRN layer, and the nc-Si embedded in an a-SiO x N y matrix, respectively. The relationship between the laser fluence, microstructure, and PL behavior of SRN films was discussed and established.